Implementasi Pembelajaran Berdiferensiasi pada Materi Teks Biografi Bahasa Indonesia Kelas X SMA - Nufi Azam Muttaqin; Kamelia Kamelia; Rahayu Pristiwati; Mukh Doyin (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
The aim of this research is to explain the implementation of differentiated strategies in learning Indonesian biographical text material for class X SMA. This research uses descriptive qualitative research methods to obtain research data in the form of information regarding the application of differentiated strategies in learning biographical text material. This research involved Indonesian language subject teachers as research respondents. Research data was obtained through observation and interviews with respondents. This research uses interview guides and observation guides as research instruments. The research results show that the implementation of differentiated strategies in learning biographical text material at Ta'allumul Huda Bumiayu Islamic High School has been implemented well. The application of differentiated learning that is carried out includes three components, including differentiation of content, process and product components. The implementation of differentiated learning has been proven to be able to increase students' motivation in participating in learning activities.